ChemInform Abstract: Discovery of N‐Substituted 3‐Arylisoquinolone Derivatives as Antitumor Agents Originating from O‐Substituted 3‐Arylisoquinolines via [2, 3] or [3, 3] Rearrangement. Issue 39 (23rd September 2014) - Li, Bo; Wang, Gaihong; Xu, Zhijian; Zhang, Yong; Huang, Xiangui; Zeng, Bubing; Chen, Kaixian; Shi, Jiye; Wang, Heyao; Zhu, Weiliang
Abstract A variety of N‐substituted 3‐arylisoquinolone derivatives are synthesized via [2, 3] or [3, 3] rearrangement reactions of corresponding O‐substituted 3‐arylisoquinolines.